(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The paper describes the current situation of libraries in ICT environment in Haryana state. Various services provided by libraries with support of Information Communication Technologies to their users have been observed and discussed with the library professionals and their users. The result of the study revealed that the ICT based resource used by the largest percent of users was the e resources.